Ann Scull land grant - Scull, Ann.
Grant issued to Ann Scull for land in Northumberland County, Va.
Wife of Benjamin Scull.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Land grants -- Virginia -- Northumberland County